Perkembangan PT BPR Aandalas Baruh Bukit Tahun 1990 – 2022 - Muhammad Ihsan; Rusdi Rusdi (Jurnal Kronologi, 2023)
People’s Credit Bank (BPR) is a type of Bank that is known to serve micro, small and medium entrepreneurs, whose locations are generally close to the community. One of the functions of BPR includes providing loans to people who have difficulty reaching conventional Banks. This research examines the development of PT BPR Andalas Baruh Bukit in 1990-2022. This research is formulated as follows: 1). How is the development of PT BPR Andalas Baruh Bukit from 1990 to 2022. 2). What are the obstacles faced by PT BPR Andalas Baruh Bukit in running its business and how to overcome these obstacles. 3). the impact of the existence of PT BPR Andalas Baruh Bukit on the Nagari Andaleh Baruh Bukit community. This study uses the historical method, with four stages as follows: Heuristics, source criticism, interpretation and historiography. Based on the research results, PT BPR Andalas Baruh Bukit underwent development, which was originally a barn pitih nagari (lpn), then changed its status to become BPR Andalas Baruh Bukit in 1990, and changed its service from initially only serving members, then participating in serving the general public. developments also occurred in the sectors of savings, credit, capital, deposits, profits. The obstacles faced by PT BPR Andalas Baruh Bukit in running its business consist of two obstacles, namely structural and non-structural. The way to overcome these obstacles is to improve the management and quality of human resources, so that rational and effective use of human resources occurs. With the establishment of PT BPR Andalas Baruh Bukit, it can increase the income of farmers and traders through business development by applying for capital loans, as well as having an impact on the lives of the local community with many employees coming from Nagari Andaleh Baruh Bukit which will indirectly help the government in reducing unemployment and poverty. in Nagari Andaleh Baruh Bukit.